Psikoseksual terhadap Fungsi Seksual Perempuan Menopause - Mentari Mentari; Jum Natosba; Jaji Jaji (Jurnal Keperawatan Silampari, 2023)
This study aims to determine the influence of psychosexuality on the sexual function of postmenopausal women in Timbangan Indralaya Utara Village. This quantitative research method has a quasi-experimental pretest-posttest research design with a control group. The results showed that the mean sexual function score before the intervention was 18.365, with a standard deviation of 6.2999. After the intervention, the mean value was 21.950, with a standard deviation of 7.2103. In the control group, the mean score of sexual function in the second measurement was 16.615 with a standard deviation of 6.1748, while the mean value in the second measurement was 16.425 with a standard deviation of 6.1482. The statistical analysis results using the t-test obtained a p-value of 0.000 or <0.05. In conclusion, psychosexuality influences the sexual function of postmenopausal women in Timbangan Indralaya Utara Village Keywords: Sexual Function, Menopause, Sexual Psychoeducation, Psychosexual